DESIGN OF PILE RAFT FOUNDATION AND DESIGN OF DEEP EXCAVATION OF CONTEMPORARY FINE ART MUSEUM - JULIAN BUDIMAN (NIM : 15013146), FERIS
The project of contemporary fine art museum is designed for fulfill the necessity of the art, particulary contemporary art and design. This Contemporary Fine Art Museum Design includes the design of the foundation and the design of deep excavation that will be used for basement. In the design process of foundation, the foundation system that has been selected is pile raft foundation. The method used for the calculation of axial bearing capacity is with manual calculation based on Meyerhoff. Then the lateral bearing capacity was calculated using Ensoft LPILE program. For the analysis of group piles, used Ensoft GROUP program. The settlement calculation was calculated using raft equivalent method. Then the settlement will be checked to raft foundation structure, this process was calculated using SETTLE 3D and SAFE programs. In the design process of deep excavation reinforcement, with secant pile as the retaining wall. The first analysis is the calculation of deep of penetration of the secant pile. Then, secant pile was modeled in PLAXIS 2D with strut reinforcement, the output of the analysis is the forces that occurred on both the secant pile structure and the strut. The design also includes steel reinforcement of the secant pile and the selection of steel profiles that will be used as the strut. The excavation must be checked for the safety factor against basal heave. Design of stell strut and also concrete structures and reinforcement of secant pile concrete structure done in accordance with the regulations of the SNI 03-1729-2015 about The Planing and Designing of Steel Structure for Building Construction and SNI 03-2847-2013 about The Planing and Designing of Concrete Structure for Building Construction. Last thing that will be analyzed in this final project is dewatering system that will be applied during construction process until the building can resist the uplift forces by its dead load.